Appraising Rufaidah Al-Aslamia, First Muslim Nurse and Pioneer of Islamic Nursing: Contributions and Legacy - Mustafa M. Bodrick; Mutlaq B. Almutairi; Fatma S. Alsolamy; Hisham M. Alfayyadh (Fakultas Ilmu Keperawatan Universitas Indonesia, 2022)
Global advancement in nursing is attributed mainly to western pioneers with negligible recognition of Rufaidah Al-Aslamia, who was the first Muslim nurse, and pioneer in Islamic nursing more than 1,400 years ago in Madinah (Medina, Saudi Arabia). She responded to the need for the provision of organized nursing care to injured soldiers in the Islamic battles during the time of Prophet Mohammed (Peace & Blessings Upon Him). The paucity of focus on Rufaidah Al-Aslamia triggered this scientific study to appraise her contributions and legacy as the pioneer of Islamic nursing. A qualitative, historical research inquiry was conducted using a research design that was exploratory, descriptive, explanatory, interpretive, and contextual within the constructivist paradigm. Data collection of literature was conducted by purposive sampling. Data analysis was conducted in two parts, which is document analysis, and thematic and content analysis with the use of deductive, inductive and abductive logical reasoning. The results of topic themes related to nurse-, patient-, and system-focused activities are provided with the emerging themes including efficient organizer, effective communication, clinical practice teacher, community care, and spiritual care. The historical narrative is reconstructed using empirical data sources as part of the discussion that includes the biography of Rufaidah Al-Aslamia and a vivid comprehensive portrayal of the contributions and legacy of Rufaidah Al-Aslamia as the first Muslim nurse and the pioneer of Islamic nursing. Abstrak Rufaidah Al-Aslamia, Perawat Muslim Pertama dan Pelopor Keperawatan Islam: Kontribusi dan Legasi. Kemajuan global di bidang keperawatan seringkali dikaitkan terutama dengan perintis barat dengan sedikit pengakuan terhadap Rufaidah Al-Aslamia, yang merupakan perawat Muslim pertama, dan pelopor dalam keperawatan Islam lebih dari 1.400 tahun yang lalu di Madinah (Arab Saudi). Rufaidah Al-Aslamia menanggapi kebutuhan penyediaan asuhan keperawatan yang terorganisir untuk tentara yang terluka dalam pertempuran Islam pada masa Nabi Muhammad (SAW). Kurangnya fokus pada Rufaidah Al-Aslamia memicu studi ilmiah ini untuk menilai kontribusi dan warisannya sebagai pelopor keperawatan Islam. Penelusuran sejarah dengan pendekatan kualitatif dilakukan dengan menggunakan desain penelitian yang bersifat eksploratif, deskriptif, eksplanatif, interpretif, dan kontekstual dalam paradigma konstruktivis. Pengumpul-an data literatur dilakukan dengan purposive sampling. Analisis data dilakukan dalam dua bagian, yaitu analisis dokumen, dan analisis tematik dan isi dengan menggunakan penalaran logis deduktif, induktif dan abduktif. Hasil dari topik yang berkaitan dengan kegiatan yang berfokus pada perawat, pasien, dan sistem disajikan dengan tema-tema yang muncul termasuk penyelenggara yang efisien, komunikasi yang efektif, guru praktik klinis, perawatan komunitas, dan perawatan spiritual. Narasi sejarah direkonstruksi menggunakan sumber data empiris sebagai bagian dari diskusi yang mencakup biografi Rufaidah Al-Aslamia dan penggambaran komprehensif yang jelas tentang kontribusi dan warisan Rufaidah Al-Aslamia sebagai perawat Muslim pertama dan pelopor keperawatan Islam. Kata kunci: Nabi Muhammad, pelopor keperawatan islam, perawat muslim pertama, Rufaidah Al-Aslamia